Equine Dental Pulp Connective Tissue Particles Reduced Lameness in Horses in a Controlled Clinical Trial - Bertone, Alicia L.; Reisbig, Nathalie A.; Kilborne, Allison H.; Kaido, Mari; Salmanzadeh, Navid; Lovasz, Rebecca; Sizemore, Joy L.; Scheuermann, Logan; Kopp, Rosalind J.; Zekas, Lisa J.; Brokken, Matthew T. (Frontiers in Veterinary Science, 2017)
Objective—To assess if injection of allogeneic dental pulp tissue particles would improve lameness in horses with naturally occurring osteoarthritis (OA) or soft tissue injury (ST). Design—Prospective, randomized, blinded, controlled clinical trial and client survey assessment. Animals—40 lame client-owned horses. Procedures— Sterile dental pulp, recovered from otherwise healthy foals that perish during dystocia, was processed under GMP to produce mechanically manipulated, unexpanded pulp tissue particles containing viable cells surrounded in extracellular matrix. Forty lame client-owned horses with confirmed OA (n=20), or ST injury (desmitis or tendonitis) received a 2 ml intra-articular (n=20 OA) or intra-lesional (n=20) injection of control transport vehicle (n=20) or 10 x 106 dental pulp tissue particles (n=20). Acclimatized horses had baseline measurements performed, and were then injected on Day 0. Horses were treadmill exercised for 2 weeks, evaluated by clinical parameters, lameness score, edema (score and circumference), pain on flexion (OA) or pressure (ST), and clients’ scores for pain and discomfort before and through 45 days after pulp injection. Twenty horses were available for > 2.5 year follow-up. Results— Pulp-treated horses showed decrease in lameness compared to baseline (P<0.009) or placebo controls (P<0.013) for at least 2 weeks. Client assessments of comfort were improved between before and 45 days after pulp injection (P<0.001). Clinical improvement with ST injury was significantly greater than OA. (P<0.001) At >2.5 year follow-up, at least 10 horses were in work. Conclusions and Clinical Relevance— Dental pulp tissue particles can be considered as a treatment option for equine lameness due to OA, desmitis or tendonitis.